2004
DOI: 10.1021/op034161+
|View full text |Cite
|
Sign up to set email alerts
|

Natural Phosphate Doped with Potassium Fluoride:  Efficient Catalyst for the Construction of a Carbon−Carbon Bond

Abstract: Natural phosphate-doped catalyst was found to be an efficient, environmentally attractive, and selective solid base catalyst for 1,4-Michael addition. The products of undesirable side reactions resulting from 1,2-adddition, polymerization, and bis-addition are not observed. The workup procedure is simplified by simple filtration with the use of natural phosphate alone or doped with potassium fluoride. Potassium fluoride-doped natural phosphate is used as catalyst for a facile synthesis of 4H-chromene under het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…A lot of supports have been introduced for increasing the basicity of KF such as KF/ZnO, KF/Ca-Mg-Al, KF/ CaO-Fe 3 O 4 , KF/celite, KF/zeolite, and KF/LDH mainly applied for organic production. Although, a majority of the abovementioned solid bases are effective in organic transformations, they suffer from some drawbacks such as low basicity, use of expensive solid supports and tedious preparation steps [17][18][19][20][21][22][23][24][25] . Montmorillonite (MMT) clay having two silica tetrahedral sheets layered between one alumina octahedral sheets.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of supports have been introduced for increasing the basicity of KF such as KF/ZnO, KF/Ca-Mg-Al, KF/ CaO-Fe 3 O 4 , KF/celite, KF/zeolite, and KF/LDH mainly applied for organic production. Although, a majority of the abovementioned solid bases are effective in organic transformations, they suffer from some drawbacks such as low basicity, use of expensive solid supports and tedious preparation steps [17][18][19][20][21][22][23][24][25] . Montmorillonite (MMT) clay having two silica tetrahedral sheets layered between one alumina octahedral sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Thus ZnCl 2 /NP has been used as excellent acidic catalyst for Friedel-Crafts alkylation [6], 1,3-dipolar cycloaddition [7], acyclonucleoside synthesis [8] and 3,4-dihydropyrimdin-2(1H)-one synthesis [9]. KF/NP catalyzed efficiently nitrile hydration [10], Michael addition [4,[11][12][13], Knoevenagel condensation [5,14], flavanone synthesis [15], nucleobase alkylation [16] and nucleoside synthesis [17]. On the other hand, we have demonstrated that Na/NP, as strongly basic catalyst, can promote Knoevenagel condensation [14], alkene epoxidation [18], Claisen-Schmidt condensation [19,20] and Michael addition [21].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the effect of water on organic reaction may be due to the high internal pressure exerted by a water solution which results from the high cohesive energy of water [42]. In literature, a number of organic reactions using natural catalysts such as clay [43][44][45][46], natural phosphates [47][48][49], animal bone [50], and various fruit juices are reported. Due to acidic nature aqueous fruit juice like lemon [51][52][53][54][55][56][57], pineapple [58], [59], coconut [60], Acacia concinna [61], Sapindus trifolistus [62] and Tamarindus indica [63] fruit has been found to be a suitable replacement for various homogeneous acid catalysts.…”
Section: Introductionmentioning
confidence: 99%